Annealing 3D printed PEKK: Investigating the impact of annealing on the mechanical, physical, and thermal properties in additively manufactured PEKK - Aaron Maloney; Eyman Manaf; Noel Gately; Ian Major; Declan M Devine (Materials & Design)
Polyetherketoneketone (PEKK) is a promising material for additive manufacturing due to its exceptional properties, making it a primary candidate for in-space manufacturing. Fused filament fabrication is a leading additive manufacturing technology for in-space manufacturing, offering advantages in terms of the manufacture of complex geometries and zero waste production. However, post-process annealing is necessary to alleviate residual stresses and optimize PEKK’s mechanical performance. This study investigates the effects of annealing on the mechanical, physical, and thermal properties of two grades of PEKK, namely PEKK-A and PEKK-SC, which are amorphous and semi-crystalline, respectively. The study examines the impact of annealing temperatures on the crystallinity and mechanical performance of the materials. Experimental results indicate that annealing at 260 °C significantly enhances the tensile and flexural properties of both PEKK-A and PEKK-SC, with a parallel increase in crystallinity. X-ray diffraction analysis reveals a phase transformation in crystal structures, with the predominance of form one crystals following annealing. Differential scanning calorimetry results further support the increase in crystallinity and molecular order, leading to improved mechanical properties. This research provides valuable insights into optimizing post-processing parameters to enhance the performance of PEKK in additive manufacturing applications.